French and Chinese Business Cooperation in Africa - Thierry Pairault (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
Although little research exists on business engagement between French and Chinese companies in Africa, Thierry Pairault offers in this policy brief many significant examples of French and Chinese engagement. While African governments want to carry out infrastructure projects at the lowest cost, they also want to ensure projects are carried out according to certain technical standards they are familiar with. Hence, at least in French-speaking countries, we see the choice of Chinese contractors to build and French engineering firms to supervise and manage. Read on to see how the future of any cooperation will lie with the business sector, and with individual firms.
Keywords: 330